Synthesis of biphasic nanomaterials based on ZnO and SnO2: application towards photocatalytic degradation of acid red dye - Kudale, Ananada S.; Kamble, Santosh B.; Gore, Anil H.; Pisal, Mahesh M.; Salokhe, Anil T.; Kolekar, Govind B.; Helavi, Vasant B. (Nano-Structures & Nano-Objects, 2019)
Zn2SnO4/SnO2 and ZnO/SnO2 biphasic nanocatalysts have been synthesized by a facile solvothermal method using ethylene glycol (EG) as solvent in three different ways maintaining the pH of the solution at either 3 or 9 followed by calcination at 700 °C. The nanocatalysts are characterized by different techniques to investigate their structure, composition, morphology and optical properties. The XRD results indicate the formation of pristine biphasic composites. The UV-absorbance and photoluminescence spectra confirms the formation of biphasic composites as well as presence of large number of defects in the prepared nanocatalysts. The biphasic nanocomposites possess better photocatalytic activity towards the degradation of Acid Red-183 (AR-183) dye than pristine SnO2 and ZnO nanoparticles. This is mainly due to better charge separation, minimal recombination rate of charge carriers and defect-riched structures of nanocatalysts.